ENDOMETRIAL STROMAL SARCOMA PADA SERVIKS UTERI - Lintong, Poppy M.; Durry, Meilany F. (Jurnal Biomedik : JBM, 2015)
Abstract: Endometrial stromal sarcoma (ESS) is a rare malignant tumor, about 0.2% of all malignant uterine tumors. Around 75% of ESS cases occur in females under 50 years, with clinical signs such as abdominal pain and bleeding per vaginam. The uterus usually enlarges, associated with polypoid tumors protruding into the uterine cavity which can be misdiagnosed with a leiomyoma. ESS occurs in the cervix, ovarium, or retroperitoneal areas, and can be derived from endometriosis in the pelvic cavity. The immunohistochemical test of the tumor cells is positive for CD10, which is typical to differ it from a leiomyoma. We reported a case of ESS in a woman of 43 years old, with a clinical diagnosis of myoma geburt. She complained of abdominal pain and a mass that came out of her vagina. Post operation, she was diagnosed as having a cervical myoma. The macroscopic examination showed enlargement of uterus tissues 15x6x7 cm, thickened endometrium, and an exophytic tumor mass (8 cm) in the cervix, with cystic and necrotic parts in it. The microscopic examination showed endometrium hypertrophy in secretion phase, cervix with endometriosis, and ESS. ESS in uterine cervix is a rare case, and in this case it is related to endometriosis in the uterine cervix. Conclusion: This case was diagnosed as endometrial stromal sarcoma in the uterine cervix based on anamnesis, physical examination, histopathological examination, and immunohistochemistry positive for CD10.Keywords: endometrial stromal sarcoma, endometriosis, uterine cervixAbstrak: Endometrial stromal sarcoma (ESS) merupakan tumor ganas yang jarang terjadi, hanya 0,2 % dari semua tumor ganas di uterus. Sekitar 75% kasus terjadi pada wanita usia di bawah 50 tahun dengan gejala klinis nyeri perut dan perdarahan melalui jalan lahir. Uterus biasanya membesar disertai tumor polipoid menonjol dalam rongga uterus dan bisa disalah diagnosis sebagai leiomioma. ESS dapat terjadi juga di serviks uteri, ovarium, retroperitoneal, dan di rongga pelvis; dapat berasal dari endometriosis. Pemeriksaan imunohistokimia dari sel-sel tumor ESS yaitu positif untuk CD10, merupakan petanda tipikal untuk membedakannya dari leiomioma. Kami melaporkan kasus ESS pada seorang wanita berusia 43 tahun dengan keluhan nyeri perut dan adanya massa jaringan yang keluar dari jalan lahir. Diagnosis klinis ialah mioma geburt dan pasca operasi diduga sebagai mioma servikal. Pemeriksaan makroskopik menunjukkan jaringan uterus membesar berukuran 15x6x7 cm, dan pada serviks terdapat massa tumor berukuran 8 cm eksofitik, dengan fokus kistik dan nekrotik. Hasil pemeriksaan mikroskopik menunjukkan serviks dengan endometriosis dan ESS. Pemeriksaan imunohistokimia positif untuk CD10. ESS pada serviks uteri merupakan kasus jarang yang berkembang dari endometriosis serviks uteri. Simpulan: Pada kasus ini diagnosis ESS pada serviks uterus ditegakkan berdasarkan anamnesis, pemeriksaan klinis, pemeriksaan histopatlogik, dan imunohistokimia CD10 positif.Kata kunci: endometrial stromal sarcoma, endometriosis, serviks uteri